The Maslahat Epistemology in Cigarette Law: Study on The Fatwa Law on Cigarettes - Iswahyudi Iswahyudi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Shaykh Ihsan Jampes gave the fatwa of the cigarette law as makruh, while Majelis Tarjih gave the fatwa haram. Although Sheikh Ihsan’s fatwa is individual, this fatwa deserves to be a comparison for the collective fatwa of the Majelis Tarjih. This is because Sheikh Ihsan’s fatwa is a complete picture of the NU fatwa in general. This paper is based on two essential questions: the two fatwas use the arguments in formulating the cigarette law and whether there are conceptual differences from these arguments. To answer these two questions, the method used is descriptive-critical-analysis with a critical hermeneutic approach. This article finds that both fatwa of Sheikh Ihsan Jampes and Majelis Tarjih have the same argument in deciding the cigarette law, namely the argument of utility or usefulness (maslahat). However, the two fatwas are various in formulating the maslahat model used. Shaykh Ihsan used maslahat tahsiniyyah while Majelis Tarjih put it in the shade of maÅŸlaá¸¥ah darÅ«riyyah. This article implies, not only from the various variants of the different choices of cigarette law but also providing insight into the epistemology that underlies these differences in law. This article educates smokers to choose between continuing or leaving smoking. Epistemology, as is well known, is open the door to one's actions. This article also provides a perspective for policy-makers between legalizing or banning cigarettes based on the theory of maÅŸlaá¸¥at.